2015
DOI: 10.1097/md.0000000000002077
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Serum Procalcitonin for Spontaneous Bacterial Peritonitis Due to End-stage Liver Disease

Abstract: Early diagnosis and prompt treatment of spontaneous bacterial peritonitis (SBP) due to end-stage liver disease is vital to shorten hospital stays and reduce mortality. Many studies have explored the potential usefulness of serum procalcitonin (PCT) in predicting SBP. The aim of this study is to evaluate the overall diagnostic accuracy of PCT levels for identifying SBP due to end-stage liver disease.After performing a systematic search of the Medline, Embase, and Cochrane databases for studies that evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
(42 reference statements)
3
17
0
Order By: Relevance
“…As regard PCT results show that: Patients in group 1 whish have spontaneous bacterial peritonitis, 95% of them have serum procalcitonin positive and 5% were negative, Patients and participants in groups 2,3,4 wish have sterile ascites or not ascetic or not cirrhotic respectively have serum procalcitonin negative in 95% PCT Negative Results Positive of them and positive in 5%. Our results were in agreement with Yang, et al 10 , who found that; Serum PCT is a relatively sensitive (95%) and specific (95%) test for the identification of SBP. However, due to the limited high-quality studies available, medical decisions should be carefully made in the context of both PCT test results and other clinical findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As regard PCT results show that: Patients in group 1 whish have spontaneous bacterial peritonitis, 95% of them have serum procalcitonin positive and 5% were negative, Patients and participants in groups 2,3,4 wish have sterile ascites or not ascetic or not cirrhotic respectively have serum procalcitonin negative in 95% PCT Negative Results Positive of them and positive in 5%. Our results were in agreement with Yang, et al 10 , who found that; Serum PCT is a relatively sensitive (95%) and specific (95%) test for the identification of SBP. However, due to the limited high-quality studies available, medical decisions should be carefully made in the context of both PCT test results and other clinical findings.…”
Section: Discussionsupporting
confidence: 93%
“…It is therefore clear that using blood for routine examinations is more convenient and safer than ascitic fluid, and the measurement of serum biomarkers has consequently received much attention recently for the early diagnosis of SBP. 10 Procalcitonin (PCT) is a precursor of calcitonin, normally secreted by C cells of the thyroid in healthy individuals. In the absence of infection, the extrathyroidal expression of the PCT gene in the liver, lung, kidney, adrenal tissue, monocytes, granulocytes, testis, prostate gland, and small intestine is suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Procalcitonin (PCT) is a 116-amino acid polypeptide precursor of calcitonin with a molecular weight of 13 KDa produced by extra-thyroidal cells (e.g., monocytes) [24]. It has been proposed in highly cited studies as a potentially valuable serum biomarker to diagnose bacterial infections in general [24][25][26] and SBP in particular [27][28][29][30]. Normally, serum PCT level is undetectable (< 0.01 ng/mL), and it rapidly increases in case of infection [26].…”
Section: Introductionmentioning
confidence: 99%
“…Serum procalcitonin was significantly higher in SBP than in sterile ascites in six of the seven which supports use of serum procalcitonin as an SBP marker. In a review by Yang et al 47 of the available data from 339 patients with LC accompanied by SBP, it was concluded that serum procalcitonin was a relatively sensitive and specific marker for the diagnosis of SBP. It has been reported that serum procalcitonin was significantly higher in cirrhotic patients with culture-positive SBP than in those with CNNA.…”
Section: Diagnostic Markers Of Sbpmentioning
confidence: 99%